Singularities of Polishing Substrates GaAs by Chemo-Dynamical and Non-Contact Chemo-Mechanical Methods - Pashchenko, G.A.; Kravetsky, M.J.; Fomin, O.V. (Physics and Chemistry of Solid State, 2015)
The comparative investigation of two chemical polishing methods as applied to GaAs substrates is carried out. In both cases the equal etchant Br2+HBr was used. The comparison of etching rates and of surface morphology is carried out. It is revealed that numerous etching pits arise during chemo-dynamical polishing of GaAs (111) В samples but not arise during non-contact chemo-mechanical polishing of the same samples. Besides, last method allows to raise appreciably etching rate as compared with the method of chemo-dynamical polishing. That is, the same etchant behaves as selective or polishing depending on method of polishing. On the basis of worked out model of substrate surface etching near line defect the simulating of etching pit arising is carried out. The results of simulation are consistent with the idea that there are two competing ways of GaAs etching in the etchant Br2+HBr .